Norm Robustness and Contestation in International Law: Self-Defense against Nonstate Actors. Issue 1 (20th February 2019) - Brunnée, Jutta; Toope, Stephen J
Abstract: Using the example of the right to self-defense under customary international law, we engage with questions concerning the linkage between norm robustness and legality. We draw out important differences between validity contestation and applicatory contestation within law. In so doing, we connect the international relations (IR) debate over norm robustness with our framework of interactional international law, bringing together constructivist insights into social normativity and a theory of international legality. We hypothesize that norms that meet the requirements of legality and are upheld by practices of legality enjoy "validity" and "facticity" (as defined by Deitelhoff and Zimmermann) and are "robust." This model reveals that law operates through a continuing process of contestation. The requirements of legality impose a discipline, such that legal contestation will normally be applicatory contestation. Through practices of legality, therefore, legal norms can be maintained or shifted. However, legal norms may decay when practices of legality weaken or when challenges amount to validity contestation. The currently heightened contestation surrounding the circumstances under which the right to self-defense can be exercised against nonstate actors allows us to explore and illustrate of these dynamics.